IMPROVING LEARNING OUTCOMES IN PERSONAL PRONOUNS LESSONTHROUGH STUDENT TEAMS ACHIEVEMENT LEARNING MODEL FOR TENTH GRADERS OF SCIENCE CLASS OF A PUBLIC SENIOR HIGH SCHOOL IN INDONESIA - Rasyidah (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2019)
To obtain optimal learning outcomes, the teacher should be able to develop and improve teaching quality and student learning activities. One of the ways to improve learning outcome is that through cooperative learning in the form of Student Team Achievement Division Model. An action research was conducted to capture the learning activities in improving learning outcomes on personal pronouns lesson of tenth graders of science class of a public senior high school in Indonesia. The method used is based on a research design with research CAR with subject of the 32 students. The result of this research indicated that student learning outcomes increased, mastery learning from 37,00% in cycle 1 of action 1 to 65,63% in cycle 1 of action 2. There are as many as 21 completed from 32 students. Then in cycle 2 action 1 reached 93,75% of students who completed the excellent category of 30 students from 32 students. As for the cycle 2 action 2, student learning outcomes that individually have reached 100% complete, and classically completeness reaches 87,19% or an average value 87,19.